ASSESSING THE FINANCIAL RESULTS OF MERGERS AND ACQUISITIONS - Cui yingying; Ashirbekova Laura (Scientific Research and Experimental Development, 2024)
A key strategy for expanding a firm, bolstering market positions, and raising the company’s worth is mergers and acquisitions (M&A). Creating synergy, or combining resources and assets to produce a larger overall effect than the sum of the individual outcomes, is the aim of the majority of transactions. One of the most challenging parts of this process is analyzing and evaluating potential financial outcomes, which is essential to the effective execution of M&A. Businesses can determine how well the transaction’s objectives—such as increased revenue, profitability, and market share—were met by analyzing the financial outcomes of mergers and acquisitions. In reality, it frequently happens that the actual outcomes deviate from the anticipated ones because of things like challenges with integration and cultural differences between businesses. When making decisions during the transaction’s planning phase, evaluation techniques like cash flow analysis and multipliers are crucial. However, M&A review should consider intangible factors like the impact on the company’s culture and brand, in addition to financial metrics. Businesses that only concentrate on financial performance may have long-term issues including decreased employee enthusiasm and the departure of important experts. An integrated approach to evaluation allows you to more accurately determine the benefits and risks of the transaction and contributes to successful integration in the long term.